Penerapan Metode C4.5 Untuk Mengklasifikasikan Kelayakan Penerima Bantuan Pangan Non Tunai (BPNT) Pada Desa Bumi Agung Marga - Yoska Aryani; Cindy Amanda Sari; Asep Afandi; Pakarti Riswanto (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2023)
Poverty is the state of not being able to meet one's fundamental needs or provide one with food, clothing, or shelter. One of the most pressing issues that the federal government needs to solve right away is poverty in Bumi Agung Marga Village. As a result, the government has made it a policy to provide citizens with social support programs including Non-Cash Food support (BPNT). In order to solve the issue, a method is needed, and one such method is data mining. In order to categorize recipients of non-cash food aid (BPNT) as eligible, the C4.5 algorithm is used. The prediction system that will be made in this study uses RapidMiner 10.2. From the results of manual calculations via Microsoft Excel using the C4.5 algorithm, it has an accuracy of 100%. data for 2021-2022, then proven by using the Rapidminer application with an accuracy of 93.33%.